COMPANY SIZE, SALES GROWTH AND LEVERAGE AGAINST TAX AVOIDANCE IN PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD OF 2012-2018 - Agung Fajar Ilmiyono; Rima Auliyamartha Agustina (STIE Binaniaga, 2020)
ABSTRACTThe difference in tax interests between companies and the government encourages companies to regulate the amount of tax burden to be paid, a strategy that is usually used by companies, namely tax avoidance, besides that the tax ratio in Indonesia has decreased from 2012-2017. This phenomenon shows that tax avoidance is still being carried out. This research aims to examine the effect of company size, sales growth, and leverage on tax avoidance in property and real estate companies listed on the IDX in the period 2012-2018. Twenty-one samples were tested with classical assumption test, using multiple regression analysis techniques. The results show that partially company size has an effect on tax avoidance, sales growth has no effect on tax avoidance and leverage has an effect on tax avoidance. Simultaneously, company size, sales growth and leverage have an effect on tax avoidance.Keywords: Leverage, Sales Growth, Tax Avoidance and Company Size